2017
DOI: 10.1097/qad.0000000000001416
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported barriers and facilitators to antiretroviral adherence in sub-Saharan Africa

Abstract: Objective:The aim of this study was to identify the range and frequency of patient-reported barriers and facilitators to antiretroviral treatment (ART) adherence in sub-Saharan Africa (SSA).Design:Studies from 2005 to 2016 were identified by searching 10 electronic databases and through additional hand and web-searching.Methods:Inclusion criteria were HIV-positive adults taking ART based in any SSA country, qualitative study or quantitative survey and included at least one patient-reported barrier or facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
109
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 167 publications
15
109
1
4
Order By: Relevance
“…This study echoes many of the findings in the above countries which revealed how low adherence to antiretroviral therapy was related to several other significant factors: fear of HIV disclosure [50, 51]; stigma and discrimination; side effects of antiretroviral drugs [49, 52]; transportation costs; and long waiting periods at health facilities to obtain antiretroviral drugs [48, 53, 54]. A further factor was the inadequate use of modern contraceptives.…”
Section: Discussionsupporting
confidence: 79%
“…This study echoes many of the findings in the above countries which revealed how low adherence to antiretroviral therapy was related to several other significant factors: fear of HIV disclosure [50, 51]; stigma and discrimination; side effects of antiretroviral drugs [49, 52]; transportation costs; and long waiting periods at health facilities to obtain antiretroviral drugs [48, 53, 54]. A further factor was the inadequate use of modern contraceptives.…”
Section: Discussionsupporting
confidence: 79%
“…Individual factors frequently cited include stigma or fear of disclosure [2,[5][6][7][8], limited knowledge about HIV and its care [7,[9][10][11], concurrent disease, (especially drug abuse) [5,7,11,12], and inadequate financial support [2, 5-7, 11, 13]. Religious and cultural beliefs [5,7,9,13], negative side effects of drugs [2,[5][6][7]11], lack of motivation to adhere to treatment [5,11,14], insufficient food support [5,11,15], work demands [5,7,[11][12][13], and lack of insurance [12,16] have also been cited as significant challenges to individual HIV care [9,12]. Community obstacles include social prompting towards herbal and alternative care, limited social support [5,7,11] and unreliable or non-existent transportation [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Religious and cultural beliefs [5,7,9,13], negative side effects of drugs [2,[5][6][7]11], lack of motivation to adhere to treatment [5,11,14], insufficient food support [5,11,15], work demands [5,7,[11][12][13], and lack of insurance [12,16] have also been cited as significant challenges to individual HIV care [9,12]. Community obstacles include social prompting towards herbal and alternative care, limited social support [5,7,11] and unreliable or non-existent transportation [5,12]. Health systems barriers in initiating and maintaining care compound these individual and community barriers to HIV care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suboptimal adherence can be due to individual, service, socio-economic and cultural factors [11][12][13][14][15][16]. Several recent systematic reviews found that suboptimal adherence to ART is associated with a range of individual, interpersonal, community and structural factors, including stigma and discrimination, forgetting, alcohol/ substance misuse, dissatisfaction/distance to healthcare facility and depression [17][18][19].…”
Section: Introductionmentioning
confidence: 99%